2021
DOI: 10.3390/catal11030351
|View full text |Cite
|
Sign up to set email alerts
|

From CO2 to Value-Added Products: A Review about Carbon-Based Materials for Electro-Chemical CO2 Conversion

Abstract: The global warming and the dangerous climate change arising from the massive emission of CO2 from the burning of fossil fuels have motivated the search for alternative clean and sustainable energy sources. However, the industrial development and population necessities make the decoupling of economic growth from fossil fuels unimaginable and, consequently, the capture and conversion of CO2 to fuels seems to be, nowadays, one of the most promising and attractive solutions in a world with high energy demand. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 215 publications
0
12
0
Order By: Relevance
“…Recently,a tomically-dispersed non-precious metal-N 4 (M-N 4 )m oieties anchored on pyrolyzed carbon (M-N 4 /C) catalysts have attracted much attention, [7] which show as ignificant impact on promoting the intrinsic CO 2 RR performance by facilitating the charge transfer from M-N x moieties to CO 2 molecular and then activating adsorbed CO 2 species. [8] Despite the most promising CO 2 RR activity obtained with M-N 4 /C catalysts,t heir catalytic performance still needs to be further improved for practical applications.C ompared to biological systems of heme-based enzymes (M-N 4 configuration), [9] it can be found that most of the currently reported M-N 4 /C catalysts are plane symmetrical structure, similar with phthalocyanine [10] or porphyrin structure. [11] Nevertheless,the plane symmetrical structure of the M-N 4 moieties usually faces ah ighreaction free energy for the water dissociation step,o wing to their sluggish proton-feeding kinetics in coupling with protons and electrons for CO production [Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,a tomically-dispersed non-precious metal-N 4 (M-N 4 )m oieties anchored on pyrolyzed carbon (M-N 4 /C) catalysts have attracted much attention, [7] which show as ignificant impact on promoting the intrinsic CO 2 RR performance by facilitating the charge transfer from M-N x moieties to CO 2 molecular and then activating adsorbed CO 2 species. [8] Despite the most promising CO 2 RR activity obtained with M-N 4 /C catalysts,t heir catalytic performance still needs to be further improved for practical applications.C ompared to biological systems of heme-based enzymes (M-N 4 configuration), [9] it can be found that most of the currently reported M-N 4 /C catalysts are plane symmetrical structure, similar with phthalocyanine [10] or porphyrin structure. [11] Nevertheless,the plane symmetrical structure of the M-N 4 moieties usually faces ah ighreaction free energy for the water dissociation step,o wing to their sluggish proton-feeding kinetics in coupling with protons and electrons for CO production [Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation reactions are typically exergonic. 1,2 However, select hydrogenation reactions relevant for the electrocatalytic production of liquid fuel from CO 2 �such as the conversion of CO 2 to formate (HCO 2 H) at standard conditions (1 atm, 298 K, pH 7)�are endergonic 3 : These endergonic hydrogenation reactions are challenging to selectively catalyze because the requisite reaction conditions also drive more accessible exergonic hydrogenation reactions such as the conversion of CO 2 to methanol (CH 3 OH) at standard conditions 4 :…”
Section: Introductionmentioning
confidence: 99%
“…There are several recent reviews on electrochemical conversion 28‐30 . and its techno‐economic aspects, 31 photochemical conversions, 32 catalytic conversion using heterocatalysts, 33 electrochemical reductions, 34 and electrocatalytic conversion, 35,36 of CO 2 to valuable products.…”
Section: Introductionmentioning
confidence: 99%
“…27 There are several recent reviews on electrochemical conversion. [28][29][30] and its techno-economic aspects, 31 photochemical conversions, 32 catalytic conversion using heterocatalysts, 33 electrochemical reductions, 34 and electrocatalytic conversion, 35,36 of CO 2 to valuable products. Additionally, there are reviews on the formation of fuels 37 and valuable products 38 from CO 2 and the comparison between different technologies.…”
Section: Introductionmentioning
confidence: 99%